The transnational cult of Mount Wutai : historical and comparative perspectives - Andrews, Susan (Specialist in Buddhism and East Asian religions); Chen, Jinhua, 1966-; Guang, Kuan (Studies on East Asian religions, 2021)
"The Transnational Cult of Mount Wutai explores the pan-East Asian significance of sacred Mount Wutai from the Northern Dynasties to the present day. Offering novel readings of comparatively familiar visual and textual sources and, in many cases, examining unstudied or understudied noncanonical materials, the papers collected here illuminate the roles that both local actors and individuals dwelling far beyond Mount Wutai's borders have played in its making and remaking as a holy place for more than fifteen hundred years. The work aims to contribute to our understanding of the ways that sacred geography is made and remade in new places and times"--